1988
DOI: 10.1002/1097-4679(198803)44:2<217::aid-jclp2270440222>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and figural gestalt completion tests with lateralized occipital area brain damage

Abstract: Verbal and figural forms of the Gestalt Completion Test were administered to 8 subjects with left or near left occipital, 12 with right or near right occipital, 12 with left anterior‐lateral and 9 with right anterior‐lateral lesions. Z score indices of verbal vs. figural scores were constructed. The indices for these groups were compared. Damage to the left occipital area did not impair the figural score more than the verbal, while damage to the right occipital area impaired the figural considerably more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The visual closure principle is the ability to visualize a complete whole when presented with incomplete information or a partial picture; thus, elements that form a closed figure tend to be grouped together (Wagemans et al, 2012). It was shown that visual closure is essential in the identification of incomplete drawings (Russell, Hendrickson, & VanEaton, 1988), of global letters (Pflugshaupt et al, 2016) and of hierarchically organized figures (Huberle & Karnath, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual closure principle is the ability to visualize a complete whole when presented with incomplete information or a partial picture; thus, elements that form a closed figure tend to be grouped together (Wagemans et al, 2012). It was shown that visual closure is essential in the identification of incomplete drawings (Russell, Hendrickson, & VanEaton, 1988), of global letters (Pflugshaupt et al, 2016) and of hierarchically organized figures (Huberle & Karnath, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, perceptual grouping depends on the integrity of a large brain network and brain damage may result in poorer performance. Indeed, damage in the right occipital lobe (Russell et al, 1988) and the medial parietal lobe, i.e., the precuneus (PC) (Pflugshaupt et al, 2016) resulted in weaker recognition performance. In adults, Gestalt perception, visual illusions or hierarchical letters are used to test aspects of the principle grouping.…”
Section: Introductionmentioning
confidence: 99%